Analysis of the Effectiveness of Digital Marketing Strategies on Customer Engagement on E-Commerce Platforms in Indonesia - Putri, Anggun Rianda; Hoer, Abdoel; Rudiyanto; putri, anggun (Ebiz Prima Nusa, 2026)
This study aims to analyze the effectiveness of digital marketing strategies in enhancing customer engagement on e-commerce platforms in Indonesia. The research focuses on examining how various elements of digital marketing, including social media activities, visual content, promotional personalization, and technology-based interactions, influence consumer engagement in digital environments. The study employs a quantitative approach by distributing questionnaires to 350 respondents who are active users of e-commerce platforms such as Shopee, Tokopedia, and Lazada within the past year. The data were analyzed using multiple linear regression to examine the influence of each variable. The results indicate that digital marketing strategies have a positive and significant impact on customer engagement, particularly in terms of content personalization and real-time interactions through features such as live chat and push notifications. These findings emphasize that the success of e-commerce platforms in enhancing consumer engagement is strongly influenced by their ability to optimize relevant and user-centered digital strategies. This study contributes to the development of more adaptive and competitive digital marketing practices within the 2025 digital business landscape.